2023
DOI: 10.3390/ijms24087541
|View full text |Cite
|
Sign up to set email alerts
|

GSK-3β Allosteric Inhibition: A Dead End or a New Pharmacological Frontier?

Abstract: Most kinase inhibitors are designed to bind to highly homologous ATP-binding sites, which leads to promiscuity and possible off-target effects. Allostery is an alternative approach to pursuing selectivity. However, allostery is difficult to exploit due to the wide variety of underlying mechanisms and the potential involvement of long-range conformational effects that are difficult to pinpoint. GSK-3β is involved in several pathologies. This critical target has an ATP-binding site that is highly homologous with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 110 publications
0
2
0
Order By: Relevance
“…Mouse entorhinal cortex and hippocampus preclinical studies have indicated that tideglusib can reduce a range of disease outcomes including tau phosphorylation, Aβ deposition, neuron loss, and gliosis, and reverse spatial memory impairment in transgenic mice. Furthermore, tideglusib's neuroprotective, anti-inflam-matory, and neurogenesis-inducing effects have also been validated in animal models [58]. In a phase 2 clinical trial with mild to moderate AD patients, tideglusib demonstrated an acceptable safety profile for a short-term (26 weeks) treatment, with the exception of a transient increase in serum transaminase levels and diarrhea (14-18 % in active, 11 % placebo).…”
Section: Gsk-3β Inhibitorsmentioning
confidence: 99%
“…Mouse entorhinal cortex and hippocampus preclinical studies have indicated that tideglusib can reduce a range of disease outcomes including tau phosphorylation, Aβ deposition, neuron loss, and gliosis, and reverse spatial memory impairment in transgenic mice. Furthermore, tideglusib's neuroprotective, anti-inflam-matory, and neurogenesis-inducing effects have also been validated in animal models [58]. In a phase 2 clinical trial with mild to moderate AD patients, tideglusib demonstrated an acceptable safety profile for a short-term (26 weeks) treatment, with the exception of a transient increase in serum transaminase levels and diarrhea (14-18 % in active, 11 % placebo).…”
Section: Gsk-3β Inhibitorsmentioning
confidence: 99%
“…Specific inhibition of GSK signaling attenuates APP cleavage by BACE1, ameliorating memory deficits in animal models [ 18 , 19 , 20 ]. GSK-3β is a key regulator of processes that underlie the development of Alzheimer’s disease; therefore, the search for its inhibitors has been widely studied [ 21 , 22 , 23 , 24 , 25 , 26 ]. These efforts led to the discovery of various selective and potent inhibitors, among which several exhibited activity in animal models of AD [ 27 ]; however, only one has reached clinical trials in humans to date.…”
Section: Introductionmentioning
confidence: 99%